Cultivating Critical Thinking Skill in Industry Revolution 4.0 Through Debating Strategy: An Action Research Based on Reflective Research - Yumelking, Marselus; Sina, Maria Wisendy (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The gap in this research is that students are never stimulated with contrastive activities using debate, so the solution is to apply debate activities in the speaking class. This type of research is Classroom Action Research. This study uses purposive sampling with a homogenous sampling method. Data were collected using debate techniques as test results and observation and interview techniques as process results. The findings of this study are that the results of the critical thinking skills test have increased to 88.5%. The test result data is supported by observation results and field notes. students can create solutions to these problems. Students listen to their opponents' ideas and are able to refute every issue that is debated. In addition, the results of field records support the results of the critical thinking test. The majority, students can actively participate during debates. They can speak and criticize their opponents' opinions. They actively refute the ideas conveyed by the opponents. The global implications of this study are the impact of debate strategies on critical thinking, language skills, psychology, learning and time management